Chili, un modèle périphérique d'insertion internationale? (Note) - Bernal-Meza, Raúl (Études internationales, 1997)
In the past few years, Chile has been noted as a model of international economic insertion of a developing country. Openness, de-regulation, exports growth, an important achievement in capturing direct foreign investment and a sustained growth, have been the elements on which the new strategy of searching for an integration with the large regional groups of trade has been supported. In the present study, we analyse the characteristics of the Chilean economy and the features that have remarked Us international insertion, in order to find the comparative advantages and disadvantages of an integration to the NAFTA and/or the MERCOSUR, providing antecedents on its foreign policy and its international economic relationships.